The secret to job satisfaction is low expectations: How perceived working conditions differ from actual ones - Simona Cicognani; Martina Cioni; Marco Savioli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
Working conditions exert a major influence on accidents and illnesses at work as well as on job satisfaction and health, yet very little research has examined the determinants of working conditions. By exploiting the Italian Labour Force Survey, this paper provides evidence on the underlying factors affecting working conditions. It provides a behavioural interpretation of the results, which stems from the discrepancy between actual and expected working conditions. In light of this interpretation, workers would declare their perceived working conditions influenced by the difference between the actual and the expected working conditions. Variables concerning personal characteristics, such as gender, education and being employed in the first job, shift expectations about working conditions and accordingly perceived working conditions. On the contrary, variables related to work characteristics, such as working full time, with shifts and in a large place, affect actual and thus perceived working conditions (negatively).
Keywords: D84; J24; J28; 330